2015
DOI: 10.1007/s11239-015-1288-1
|View full text |Cite
|
Sign up to set email alerts
|

Universal, class-specific and drug-specific reversal agents for the new oral anticoagulants

Abstract: Although there is controversy about the absolute need for a reversal agent for the new direct oral anticoagulants (DOACs), the absence of such an agent is a barrier to more widespread use of these agents. For the management of major life-threatening bleeding with the DOACs, most authorities recommend the use of four factor prothrombin complex concentrates, although the evidence to support their use in terms of improving outcomes is meager. At the present time, there are three antidotes in development and poise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
(16 reference statements)
0
22
0
3
Order By: Relevance
“…With its high degree of protein binding of 92–95% [3], rivaroxaban is regarded as non-dialyzable, as also suggested by results from a clinical study conducted by Dias et al [5]. Since protein binding is regarded as not a limiting factor in hemoperfusion [6], the removal of rivaroxaban, as for example by commonly available coated charcoal cartridges, has been deemed possible, but experimental evidence is still lacking [7]. While Andexanet alfa may offer a promising approach to reverse the FXa inhibitor-mediated anticoagulation of rivaroxaban, it has not yet been approved [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With its high degree of protein binding of 92–95% [3], rivaroxaban is regarded as non-dialyzable, as also suggested by results from a clinical study conducted by Dias et al [5]. Since protein binding is regarded as not a limiting factor in hemoperfusion [6], the removal of rivaroxaban, as for example by commonly available coated charcoal cartridges, has been deemed possible, but experimental evidence is still lacking [7]. While Andexanet alfa may offer a promising approach to reverse the FXa inhibitor-mediated anticoagulation of rivaroxaban, it has not yet been approved [8].…”
mentioning
confidence: 99%
“…b Inlet/outlet rivaroxaban plasma concentrations, ( c ) extraction ratios R e = (c in – c out )/c in and plasma clearances CL = Q B  × (1 – Hct) × R e [7] during 120 min blood recirculation through the miniaturized CytoSorb columns (mean ± SD, n = 2). CL values were calculated considering the mean hematocrit calculated from the values measured at the start and the end of each experiment (0.349 ± 0.018, n = 4).…”
mentioning
confidence: 99%
“…It has been studied with rivaroxaban, apixaban, and low-molecular-weight heparin (81). Infusion of andexanet alfa was able to quickly normalize several laboratory assays in randomized controlled trials of healthy elderly volunteers (82).…”
Section: New Anticoagulant Medication-related Ichmentioning
confidence: 99%
“…Andexanet has no known hemostatic effects. It did reduce tissue factor pathway inhibitor levels, which may imply a prothrombotic effect (81). The ANNEXA-4 trial demonstrated that an initial bolus and subsequent 2-h infusion of andexanet substantially reduced anti-factor Xa activity in patients with acute major bleeding associated with FXa-I, with effective hemostasis occurring in 79% (83).…”
Section: New Anticoagulant Medication-related Ichmentioning
confidence: 99%
See 1 more Smart Citation